과민성장증후군 - 차보람; Boram Cha; 신정은; Jeong Eun Shin; 나우리; Woori Na; 김성은; Sung Eun Kim; 이주엽; Ju Yup Lee; 유혜수; Hyesu You; et al. (The Korean journal of gastroenterology, 2025)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by recurrent abdominal pain in the absence of detectable organic, systemic, or metabolic disease. According to the Rome IV criteria, symptoms must have begun at least six months before and be present during the preceding three months for diagnosis. The proposed mechanisms underlying IBS include abnormal intestinal motility, visceral hypersensitivity, altered brain-gut interactions, low-grade mucosal inflammation, immune dysregulation, genetic predisposition, and gut microbiota imbalance. Although many patients report food-related symptom triggers, the relationship between dietary or lifestyle factors and IBS is unclear. The Diet, Obesity, and Metabolism of the Korean Society of Neurogastroenterology and Motility addressed this gap by developing visual educational materials on dietary and lifestyle strategies for functional gastrointestinal disorders. This review summarizes the section devoted to IBS and provides a comprehensive overview of its practical recommendations for clinicians and patients.